The implementation of multigrid method for solving heat equation of thermal control system on printed circuit board - Alias, Norma; A. Ghaffar, Zarith Safiza; Hamzah, Norhafiza; Satam, Noriza; M. Murid, Ali Hassan (Faculty of Science, Universiti Teknologi Malaysia, 2009)
Thermal interaction between electronic components can cause temperature increasing on printed circuit board (PCB) that influences its performance. Due to this problem, thermal control system can be used in order to achieve high performance of electronic system. The numerical simulation which based on one dimensional heat equation is used to obtain the temperature profile of PCB. This paper concentrates on implementation the preconditioner scheme called V-cycle multigrid method in solving thermal control system on PCB. Numerical iterative method of red black Gauss Seidel (GSRB) is used for smoothing process of V-cycle type. This paper will proposed the restriction and interpolation process to decrease and increase of the grid size of PCB. The result obtained will be compare with non-multigrid method. Numerical analysis evaluation under consideration are time execution, computation complexity, number of iterations, accuracy and convergence rate.